Analysis of immunoglobulin/T‐cell receptor repertoires by high‐throughput RNA sequencing reveals a continuous dynamic of positive clonal selection in follicular lymphoma - Victor Bobée; Mathieu Viennot; Vinciane Rainville; Liana Veresezan; Fanny Drieux; Pierre‐Julien Viailly; Victor Michel; Vincent Sater; Marie‐Delphine Lanic; Elodie Bohers; Vincent Camus; Hervé Tilly; et al. (HemaSphere, 2024)
Abstract Follicular lymphoma (FL) course is highly variable, making its clinical management challenging. In this incurable and recurring pathology, the interval between relapses tends to decrease while aggressiveness increases, sometimes resulting in the transformation to higher‐grade lymphoma. These evolutions are particularly difficult to anticipate, resulting from complex clonal evolutions where multiple subclones compete and thrive due to their capacity to proliferate and resist therapies. Here, to apprehend further these processes, we used a high‐throughput RNA sequencing approach to address simultaneously the B‐cell immunoglobulin repertoires and T‐cell immunoglobulin repertoires repertoires of lymphoma cells and their lymphoid microenvironment in a large cohort of 131 FL1/2‐3A patients. Our data confirm the existence of a high degree of intra‐clonal heterogeneity in this pathology, resulting from ongoing somatic hyper‐mutation and class switch recombination. Through the evaluation of the Simpson ecological‐diversity index, we show that the contribution of the cancerous cells increases during the course of the disease to the detriment of the reactive compartment, a phenomenon accompanied by a concomitant decrease in the diversity of the tumoral population. Clonal evolution in FL thus contrasts with many tumors, where clonal heterogeneity steadily increases over time and participates in treatment evasion. In this pathology, the selection of lymphoma subclones with proliferative advantages progressively outweighs clonal diversification, ultimately leading in extreme cases to transformation to high‐grade lymphoma resulting from the rapid emergence of homogeneous subpopulations.